2013
DOI: 10.1371/journal.pone.0074242
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Plus Concurrent or Sequential Temozolomide for Glioblastoma in the Elderly: A Meta-Analysis

Abstract: BackgroundMany physicians are reluctant to treat elderly glioblastoma (GBM) patients as aggressively as younger patients, which is not evidence based due to the absence of validated data from primary studies. We conducted a meta-analysis to provide valid evidence for the use of the aggressive combination of radiotherapy (RT) and temozolomide (TMZ) in elderly GBM patients.MethodsA systematic literature search was conducted using the PubMed, EMBASE and Cochrane databases. Studies comparing combined RT/TMZ with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
1
49
1
1
Order By: Relevance
“…In this analysis, treatment using SRT with concurrent TMZ correlated with an improved survival, which was also the trend for patients aged ≥75 years. This finding is supported by previously published studies reporting increased overall survival in elderly GBM patients since the TMZ era, as well as a recently published meta-analysis of non-randomized studies of elderly GBM patients treated with RT and concurrent TMZ or RT alone, who also exhibited improved survival (21)(22)(23).…”
Section: Discussionsupporting
confidence: 81%
“…In this analysis, treatment using SRT with concurrent TMZ correlated with an improved survival, which was also the trend for patients aged ≥75 years. This finding is supported by previously published studies reporting increased overall survival in elderly GBM patients since the TMZ era, as well as a recently published meta-analysis of non-randomized studies of elderly GBM patients treated with RT and concurrent TMZ or RT alone, who also exhibited improved survival (21)(22)(23).…”
Section: Discussionsupporting
confidence: 81%
“…A recent meta-analysis revealed a clear survival benefit of RT + TMZ in elderly patients with glioblastoma, where it was shown that combined RT + TMZ reduced the risk of death and progression compared with RT-alone [31]. Although we did not perform a sub-group analysis based on patients' age in the present study, the results from Yin et al [31] reveal a clear beneficial effect of TMZ in elderly patients as well.…”
Section: Discussioncontrasting
confidence: 52%
“…We were not able to perform a subgroup analysis based on the MGMT methylation status due to lack of reported data. Moreover, a subgroup analysis of the elderly was not performed, but there is enough evidence to support the survival benefit of TMZ in this population [31,37]. In addition, we did not perform analysis of toxicity due to incomplete reporting of adverse events, which further prevented the full consideration of TMZ as a concomitant treatment along with radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing proportion of elderly GBM patients [28,29], it is important to focus on improving outcomes in this population and clarifying the standard of care. Recent studies have suggested the utility of aggressive multimodal treatment of elderly GBM patients [19,30].…”
Section: Age At Diagnosismentioning
confidence: 99%